Reinventing the University: Managing and Financing Institutions of Higher Education. - Williams, Doyle Z.; Boatsman, Jame R. (The Accounting Review, 1996)
Abstract Reviews the book "Reinventing the University: Managing and Financing Institutions of Higher Education," edited by Sandra L. Johnson and Sean C. Rush.